TMT-based quantitative proteomics analysis reveals the role of Notch signaling in FAdV-4-infected LMH cell - Niu, Yujuan; Liu, Zhiyang; Wang, Mengyu; Du, Ke; Chang, Kaihui; Ding, Yonghe (Frontiers in Microbiology, 2022)
Fowl adenovirus serotype 4 (FAdV-4) is recognized as a pathogen that causes hydropericardium syndrome (HPS). Irrespective of the pathway used by the virus to invade the chicken, the pathological characteristics of the disease include degeneration and necrosis of hepatocytes, formation of intranuclear inclusions, as well as inflammatory cell infiltration. Liver dysfunction constitutes one of the critical factors leading to death. Therefore, it is vital to investigate the virus-mediated severe pathological liver damage to further understand the pathogenesis of FAdV-4. Here, proteomics, a tandem mass tag (TMT)-based approach to directly analyze protein expression, was used to determine the protein expression during FAdV-4 proliferation in leghorn male hepatoma (LMH) cells. We identified 177 differentially expressed proteins associated with various biological processes and pathways. The functional enrichment analysis revealed that FAdV-4 could downregulate some signaling pathways in LMH cells, including NOD-like receptor signaling, RIG-I-like receptor signaling, NF-κB signaling, TNF signaling pathway, and Notch signaling, FoxO signaling, PI3K-Akt signaling, and autophagy. The results of proteomics screening suggested an association between FAdV-4 infection and Notch signaling in LMH in vitro, indicating that Notch signaling regulated the expression of inflammatory cytokines and interferons but not viral replication in LMH cells. These data contributed to the understanding of the immunopathogenesis and inflammopathogenesis of FAdV-4 infection and also provided valuable information for the further analysis of the molecular mechanisms underlying viral pathogenesis.